БЎЛАЖАК ЎҚИТУВЧИЛАРНИНГ ЎҚУВ – БИЛИШ ФАОЛИЯТИНИ РИВОЖЛАНТИРИШДА ИНТЕРФАОЛ МЕТОДЛАР - Пазылова, М.Е. (ILIM hám JÁMIYET, 2021)
In this article, the pedagogical teachings created by our thinker-ancestors will give future teachers the opportunity to develop their professional skills and develop their educational and cognitive activities, and the learning movement can provide effective and professional training for future teachers.